The Relationship Between Emotional Quotient With Form 4 Students' Academic Achievement - Yahaya, Noordin (2006)
ABSTRACT: The purpose of this study is to examine the relationship between emotional intelligence and students’ academic achievement. It also aimed to determine the relationship between the problems faced by the students, such as peers influence, family problem and financial problem also, the method that they use to maintain the emotional such as meet the counselor, story to friends, jogging and knowing in religion, with the students’ academic achievement. The respondents consist of 399 form 4 students from ten primary schools in three states, such as Johor, Kelantan and Terengganu. Descriptive Statistic was used to analyze emotional intelligence, problem faced and the method that used to maintain the emotional: percentage, mean and standard deviation. Inferential Statistic that is Pearson Correlation Analysis was used to analyze the correlation between emotional intelligence and students’ academic achievement. The finding shows a significance of 0.162. However, the analysis also shows there are relationships between method of story to friends and jogging with the students’ academic achievement meanwhile there are no relationship between peers influence, family problems, financial problems, method of met counselor and method of knowledge in religion with the students’ academic achievement. (Keywords: emotional intelligence and students’ academic achievement, peers influence, family problem and financial problem and method)